2021
DOI: 10.3389/fmars.2021.791965
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Crustacean Female Sex Hormone 1a in a Protandric Simultaneous Hermaphrodite Shrimp

Abstract: Crustacean female sex hormone (CFSH) plays a pivotal role in the development of secondary sex characteristics in dioecious crustaceans. However, until now the knowledge concerning its functions in hermaphroditic species is scanty. Herein, we explored the function of CFSH (Lvit-CFSH1a) in the peppermint shrimp Lysmata vittata, a species characterized by a rare reproductive system of protandric simultaneous hermaphroditism (PSH). Lvit-CFSH1a cDNA was 1,220-bp in length with a 720-bp ORF encoded a polypeptide of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Our results confirmed the inhibitory effect of EsCFSH-1 to EsIAG in the AG, which agree with the finding in the mud crab S. paramamosain (Liu et al, 2018). We also found the inhibitory effect of EsIAG to EsCFSH-1 in the EG of male and female, which is supported by the finding in the peppermint shrimp L. vittate (Liu et al, 2021a;Liu et al, 2021c). Our study confirmed the existence of the regulatory feedback loop between EsCFSH-1 and EsIAG.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed the inhibitory effect of EsCFSH-1 to EsIAG in the AG, which agree with the finding in the mud crab S. paramamosain (Liu et al, 2018). We also found the inhibitory effect of EsIAG to EsCFSH-1 in the EG of male and female, which is supported by the finding in the peppermint shrimp L. vittate (Liu et al, 2021a;Liu et al, 2021c). Our study confirmed the existence of the regulatory feedback loop between EsCFSH-1 and EsIAG.…”
Section: Figuresupporting
confidence: 92%
“…Compared to the normal crabs, we found that the intersex crabs show the aberrant expression of EsCFSH-1 and EsIAG . Normally, CFSH-1 expressed at the highest level in the female EG ( Kotaka and Ohira, 2017 ; Liu et al, 2018 ; Liu et al, 2021a ) and IAG extremely highly expressed in the male specific organ AG ( Sagi and Aflalo, 2005 ). For the intersex crabs, the expression of EsCFSH-1 and EsIAG in the EG and AG was close to the male level.…”
Section: Discussionmentioning
confidence: 99%
“…CFSH-dsRNA injection had no significant effects on transcript levels of 3βHSD in adult-female-specific tissues but decreased expression levels of 17βHSD8a, 17βHSD8b , and ERR in a tissue-specific manner, indicating these genes were unlikely to be directly regulated by CFSH . Previous studies demonstrated that CFSH might not be involved in ovarian development ( 19 , 64 ). However, the significantly reduced transcript level of 17βHSD8b in the ovary of adult females injected with CFSH-dsRNA may affect the metabolic efficiency of E2 leading to changes in ovarian differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, its homolog has been successfully identified in several other decapod species such as the swimming crab P. trituberculatus [96], the Chinese mitten crab Eriocheir sinensis [97], the green shore crab C. maenas [98] and the mud crab Scylla paramamosain [99][100][101], the kuruma prawn M. japonicus [102], the Pacific white shrimp Litopenaeus vannamei [97], the banana shrimp Fenneropenaeus merguiensis [103], the Antarctic shrimp Chorismus antarcticus [104], the Eastern rock lobster S. verreauxi [105], the giant freshwater prawn M. rosenbergii [97,106,107], the peppermint shrimp Lysmata vittata [108,109], the red swamp crayfish Procambarus clarkii [96], and the Australian crayfish C. quadricarinatus [110]. RNA interference of CFSH caused the anomalous development of female reproductive characteristics including ovigerous setae, gonopores, and extended parental brood care in Callinectes sapidus [95], and the formation of gonopores in juvenile stages in the mud crab [100].…”
Section: Decapod Crustaceans As a Treasury Box Of Diverse Sex Differe...mentioning
confidence: 99%
“…Taken together, accumulating CFSH studies indicate that it might regulate female secondary reproductive phenotypes in some crab species, and is not a female-specific hormone in other decapod species. Although a new potential function of CFSH has been reported to be its involvement in growth [108], more comparative analysis will be required for comprehensively understanding its physiological roles.…”
Section: Decapod Crustaceans As a Treasury Box Of Diverse Sex Differe...mentioning
confidence: 99%